Towards an understanding of competing constructions of risk for impact assessment - Day, Kirsten D (Department of Environmental and Geographical Science, 2022)
Since the inception of the Impact Assessment (IA) tool in the late 4567s, a pivotal role has been assigned to science and expert knowledge, in a rational scientific approach to anticipating the environmental effects of proposed projects. Embedded in this philosophy is a realist interpretation of risk, such that measurable properties are allocated that can be determined based on probabilities. The intention is to reduce uncertainty and improve the accuracy of forecasting. Whilst this approach adds value to IA, it has limitations in respect of the human dimensions of risk which influence the process and outcomes of the assessment. This research responds to this problem with an exploration into competing constructions of risk for the IA discipline. I begin this thesis by highlighting how IA has been affected by the passage of risk, over several decades, from the domain of science to a wider public discourse linked to fear and anxiety about living in a “Runaway World” (Giddens, L77L). Relevant in this context, are espoused sustainability principles for IA relating to inclusivity and equity. Underscored by numerous critics are associated challenges, particularly when it comes to incorporating social values and acknowledging the role of power in IA. I propose that these challenges can be linked to interpretations of risk - realist on one hand, and societal, cultural and cognitive on the other. The approach to uncovering the implications of competing constructions of risk for IA relies on the method of critical discourse analysis (CDA), and a Foucauldian notion of discourse linked to power. I describe three distinct theories focusing on the social, psychological, and cultural dimensions of risk. These include risk society theory, the psychometric paradigm and cultural theory. To demonstrate their relevance, each theory is applied in a discourse analysis of three South African case studies: a specialist study for a fuel storage facility, an environmental impact assessment (EIA) for a nuclear power plant, and a strategic environmental assessment (SEA) for proposed hydrofracking for shale gas in the Karoo. The studies highlight limitations to the realist interpretation of risk, particularly in morally and politically contested circumstances. My argument is for a richer understanding of risk for IA, along a continuum which accommodates pluralism. I conclude that alternative risk theories provide deeper insight into social values and power dynamics, with a view to advancing the IA discipline to meet the challenges posed by increasing levels of uncertainty in an everchanging world.